Sharing in Their Daily Routines, Joys and Sorrows: Notes from Zambia - Mrowca, Natalia (Roczniki Kulturoznawcze, 2023)
This article is a subjective account of a three-month stay in northern Zambia to carry out research and do volunteer assistance. Written from the perspective of a Polish student of Applied Anthropology, the text shows a gradual change in the Author’s perception of the surrounding new reality, the difficulty of avoiding culture shock, and facing cultural obstacles that, despite preparation, are difficult to be ready for. The main objective, however, is to try to enter the local environment, understand the behaviour, beliefs of Zambians and establish a relationship with the locals. By conducting research on Zambian culture and research on the human flourishing of social life leads, observations are enriched by real conversations with Zambians who open up to the interviewee and enter into a cross-cultural dialogue.